An Efficient Downloading Service of Large Popular Files in VANET Based on 802.11p Protocol - Weicheng Zhao; Yajuan Qin; Yujun Cheng (International Journal of Distributed Sensor Networks, 2015)
With the improvement of technology and the increasing demand for convenience and comfort, new interests have emerged in commercial and entertainment service in VANET. The downloading service of large popular files has played a crucial role for those commercial and entertainment service application. In this paper the author proposed an efficient scheme to help vehicle nodes download the large popular files from the Road Side Unit (RSU). Due to the constraint density of RSU and high mobility of vehicle nodes, vehicle nodes cannot download the whole large files from RSU before they move out of the communication range. To deal with this problem, we proposed multiple access modes downloading schemes: vehicles download files from RSU directly, vehicles download files through relay vehicles, and vehicles download files through other vehicles. We give credit-based incentives for relay vehicle selection to guarantee the stability and quality of the link bandwidth. We also proposed a game theory-based way to control number of neighbors reply packets, which does not cost additional bandwidth resource and ensure integrity of the files. Finally, simulations show that our proposed schemes performed well in high mobility VANET environment and ensure the data integrity.